Metrology of Mo/Si multilayer mirrors at 13.5 nm with the use of a laser-produced plasma extreme ultraviolet (EUV) source based on a gas puff target - Rakowski, R.; Bartnik, A.; Fiedorowicz, H.; Jarocki, R.; Kostecki, J.; Krzywiński, J.; Mikołajczyk, J.; Pina, L.; Ryc, L.; Szczurek, M.; Ticha, H.; Wachulak, P. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
In this paper an application of a recently developed laser plasma source of extreme ultraviolet (EUV) for optical measurements of optical characteristics of Mo/Si multilayer mirrors is presented. The source is based on an xenon-helium double-stream gas puff target irradiated with laser pulses from a Nd : YAG laser system (E = 0.55 J, t = 3.9 ns, f = 10 Hz, M 2 = 2.5). The results show that the source can be useful for EUV lithography technologies as a metrology tool in the semiconductor industry.
Optica Applicata, Vol. 36, 2006, nr 4, s. 593-600
Keywords: optyka; laser-produced plasma extreme ultraviolet (EUV) source; gas puff target; Mo/Si mirrors; EUV spectroscopy